URGENSI FILSAFAT DAN AGAMA DALAM KEHIDUPAN MASYARAKAT INDONESIA: TINJAUAN FILSAFAT AGAMA TERHADAP KEMATIAN PASCA PANDEMI - Fuad Noorzeha; Agus Sutono (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2021)
Philosophy of religion is not focused on a particular religion, but rather on explaining the main points of religious teachings in general and includes all components of thought and teachings related to the interests of human essential life. Death is a part of human life that cannot be explained empirically. Thus, death becomes an eternal problem for humans. In this study, the death of the philosophy of religion perspective is a form of awareness of the reality of metaphysical-existential life. Thus, the synergy between heart in religion and reason in philosophy becomes one as an objective approach to death. The process of death during a pandemic is an acknowledgment of human existence in this limited world. The purpose of this paper is the importance of understanding philosophy and religion in the philosophy of religion in human life. Especially the meaning of death during a pandemic and after the Covid-19 pandemic. This research is library research with a qualitative method that involves the point of view of religious philosophy in seeing the meaning of post-pandemic death in a rational-philosophical manner. Thus, death is no longer a matter that is always debated, but death does not need to be worried and worried but must be faced by preparing it through the provision of religious understanding and a good attitude of religiosity. Therefore, this research is considered important to provide a critical view of the meaning of death from the point of view of religious philosophy.